Assessing the impact of freewriting and peer editing techniques on writing skills: An experimental study on personal recount texts in the context of education - Widyawati, Irma (Asian Journal Collaboration of Social Environmental and Education, 2025)
Background: Writing plays a crucial role in helping students communicate their ideas in various situations. However, tenth-grade students at SMA N 1 Wanadadi face challenges in writing, such as a lack of vocabulary and difficulties understanding grammar and text structure. This study aimed to assess the effectiveness of Free Writing and Peer-Editing techniques in improving students' ability to write personal recount texts. Methods: This research utilized an experimental design with a quantitative approach. The population consisted of 360 tenth-grade students at SMA N 1 Wanadadi, with XA class as the experimental group and XB class as the control group. Data were collected using pretests and post-tests in written form. The data were analyzed using IBM SPSS Statistics 23. Findings: The results of the t-test showed that t count (6.319) was greater than the t value (2.030), and the significance (Sig = 0.000) was less than 0.050. This indicates that the Null Hypothesis (Ho) is rejected, and the Alternative Hypothesis (Ha) is accepted, proving that Free Writing and Peer-Editing techniques effectively enhance students' ability to write personal recount texts. Conclusion: The use of Free Writing and Peer-Editing techniques is effective in improving the tenth-grade students' ability to write personal recount texts at SMA N 1 Wanadadi Banjarnegara. Novelty/Originality of this Study: This study contributes to the body of knowledge by demonstrating the effectiveness of Free Writing and Peer-Editing techniques in a high school setting, specifically for students struggling with writing personal recount texts. The combination of these two techniques offers a practical approach to enhancing writing skills in a classroom where students face language-related difficulties.